2001
DOI: 10.1017/s0022112001006115
|View full text |Cite
|
Sign up to set email alerts
|

The motion of a singular vortex near an escarpment

Abstract: McDonald (1998) has studied the motion of an intense, quasi-geostrophic, equivalentbarotropic, singular vortex near an infinitely long escarpment. The present work considers the remaining cases of the motion of weak and moderate intensity singular vortices near an escarpment. First, the limit that the vortex is weak is studied using linear theory. For times which are short compared to the advective time scale associated with the vortex it is found that topographic waves propagate rapidly away from the vortex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…These theoretical results were confirmed by contour dynamics model simulations. Dunn et al (2001) extended the previous work to weak and medium intensity vortices. They showed that vortices moving against topographic waves radiate energy and move towards the shelf while vortices moving with the topographic waves can reach a steady state.…”
Section: Introductionmentioning
confidence: 56%
“…These theoretical results were confirmed by contour dynamics model simulations. Dunn et al (2001) extended the previous work to weak and medium intensity vortices. They showed that vortices moving against topographic waves radiate energy and move towards the shelf while vortices moving with the topographic waves can reach a steady state.…”
Section: Introductionmentioning
confidence: 56%
“…Therefore, Figs 14 and 15 simulate qualitatively the generation of vortices by non‐linear waves. This ill‐understand phenomenon has only lately begun to be studied (Bühler & Jacobson 2001; Dunn et al 2001; Galiev & Galiev 2001; Galiev 2002).…”
Section: Topographic‐resonant Amplification Of Weakly Nonlinear Seimentioning
confidence: 99%
“…Further development of the theory of point vortices is reflected in monographs and reviews [6][7][8][9][10][11][12][13][14][15][16]. The classical concept of point vortices was used in problems of meteorology [17][18][19][20][21][22][23] and oceanography in [24][25][26][27][28][29][30]. Gryanik first generalized the theory of two-dimensional vortices to the case of a two-layer [31] and then to an N-layer rotating fluid [32].…”
Section: Introductionmentioning
confidence: 99%